2021
DOI: 10.25115/eea.v39i6.5084
|View full text |Cite
|
Sign up to set email alerts
|

The role of money in employees’ life: Connection with psychological characteristics of the company staff

Abstract: In the course of empirical research, a connection was established between the psychological characteristics of employees (social-psychological attitudes, job satisfaction and life satisfaction) and their assessment of the role of money in their lives. There is a positive statistically significant relationship between such social-psychological attitudes of company staff as the focus on “result”, “selfishness”, “freedom”, “power”, “work” and their assessment of the role of money in life (as the degree of such so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study indicated a positive relationship between job satisfaction and compensation, with men reporting higher levels of job satisfaction and earning more than their female colleagues. According to a research by Karamushka et al (2021), there is a significant association between workers' job satisfaction, life satisfaction, and attitudes towards money. Because employees only consider their salaries and occasionally regard them as the only source of motivation, it can be claimed that attitude towards money affects employee attitudes at work (Khawaja, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study indicated a positive relationship between job satisfaction and compensation, with men reporting higher levels of job satisfaction and earning more than their female colleagues. According to a research by Karamushka et al (2021), there is a significant association between workers' job satisfaction, life satisfaction, and attitudes towards money. Because employees only consider their salaries and occasionally regard them as the only source of motivation, it can be claimed that attitude towards money affects employee attitudes at work (Khawaja, 2017).…”
Section: Introductionmentioning
confidence: 99%